Analisis Dan Perancangan Sistem Point Of Sales (POS) Pada Toko Harco Bali - Stefani Yohana Paula Bere; Ni Made Estiyanti; Nengah Widya Utami (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2023)
Toko Harco Bali is a company that sells electronic equipment. In the system that is running at the Toko Harco Bali, it is still done manually such as making notes which often have errors when calculating the total payment, there is no recording of customer data & inventory records that are still written in notebooks and make time less effective, as well as the lack of existing internal control activities so as to make employees take concurrent jobs. Point Of Sales (POS) is a system to process sales transactions of goods. Internal control is one of the systems to guarantee the security of the company. The purpose of this research is to analyze and design the point 0f sales system. In this design, the system can provide convenience and security in the transaction process. The research method used is the system development method, namely the prototyping approach. The stages in the prototyping method are, design or planning and end in the design of a new proposed system. The results of the analysis of SPI components in the form of control environment, risk assessment, information and communication, supervision and control activities and the results of this research design in the form of Database DFD, ERD and interface design